1993
DOI: 10.1016/s0022-5347(17)36229-8
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Carcinoma Producing Granulocyte Colony-Stimulating Factor: A Case Report

Abstract: A 67-year-old man with squamous cell bladder carcinoma showed remarkable leukocytosis (maximum 50,300 per microliter.) for 4 months while the neoplasm recurred and metastasis progressed. The patient died of systemic metastasis within 9 months after cystectomy. Enzyme immunoassay of the serum demonstrated remarkably high levels of granulocyte colony-stimulating factor (4,928 pg./ml.). Immunohistochemical examination with anti-granulocyte colony-stimulating factor monoclonal antibody demonstrated granulocyte col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Our case showed an aggressive clinical course as reported in G-CSF-producing tumors originating from other organs [7,9] . The production of such a hematopoietic factor seems to have prognostic implications in prostate cancer, too.…”
Section: Color Version Available Onlinesupporting
confidence: 77%
See 1 more Smart Citation
“…Our case showed an aggressive clinical course as reported in G-CSF-producing tumors originating from other organs [7,9] . The production of such a hematopoietic factor seems to have prognostic implications in prostate cancer, too.…”
Section: Color Version Available Onlinesupporting
confidence: 77%
“…Several cases with G-CSF-producing cancer of the lung and urinary bladder have been reported in which the G-CSF genes were expressed even in the primary tumor specimens and in which leukocytosis became overt after the tumors metastasized [7] . The present case also showed leukocytosis during the course of the disease despite a normal white blood cell count at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In some patients, the leukocytosis has an identifiable nonparaneoplastic etiology, most commonly infection, tumor necrosis, or glucocorticoid administration; none of these causes were identified in our patient. Leukocytosis with apparent expression of granulocytecolony stimulating factor (G-CSF) has been previously reported in SCC of the uterine cervix [10], urinary bladder [11], ureter [12], head and neck [13], and lung [14]. Although serum studies for elevated G-CSF were not performed in this case, it is likely that the gastric SCC was in some way associated with the patient's persistent leukocytosis given the rapid resolution after surgical removal of the neoplasm.…”
Section: Discussionmentioning
confidence: 81%
“…Most G-CSFeproducing tumors are poorly differentiated and are likely to develop distant metastases. 8,11,12,[14][15][16][17][19][20][21][22] G-CSF stimulated the growth of a nonhematopoietic malignant cell line in vivo, 28 and G-CSF was also considered to be a major autocrine growth factor in rapid tumor proliferation and metastasis. 29 It has also been suggested that G-CSF has a priming effect on platelet aggregation and thrombin generation and subsequently induces a hypercoagulable state.…”
Section: Discussionmentioning
confidence: 99%